La problemática transición boliviana hacia la época postneoliberal: el caso de la economía comunitaria - Nam Kwon Mun (Revista de Estudios Sociales, 2015)
The government of Evo Morales has defined the contemporary era in Bolivia as the time of post-neoliberalism, a period of transition toward communitarian socialism through economic pluralism and integral economic development. The multiple paths to development among the diverse forms of production, each based on its own logic, mark the way in which it differs from other existing models. However, the evolution of the communitarian economy, which is the pillar of the new model, demonstrates through the results of the agrarian reform and the agricultural revolution that the continuance of neoliberal paradigms has perpetuated the hegemonic capitalist pattern of development. Contemporary Bolivia is thus immersed in a radical anti-neoliberal rhetoric tempered by neoliberal pragmatism.